Transformation. Issue 1 (March 2021) - Twining, William
Abstract: This brief paper is an account of Peter Fitzpatrick's appointment to the Faculty of Law at Queens University, Belfast, and his consequent transformation, personally and professionally, during his short tenure at Queens.